The Importance Of Schools’ Sport Promotion In Society, - Gündoğdu, C., Yüksel, G., Yücel, A. S., Imanzadeh, M., Bingöl, H., (My University, 2012)
This study aims to generalize of school sports in the society, and this indicates how it impresses to the achievement of sporty.The universe of the research constitues physical education teachers work at schools of Ministry of National Education. The sample of research constitutes is composed twenty-six female and one hundred-two male physical education teachers, who work in the center of Elazig. A questionnaire is applied as a data collection device, these rates and frequency values of the questionnaire data are considered, and these values put into tables. Consequently, physical education teachers participated in this research stated that; %85.1 (109 people) considers that school sports would be affective for spreading schools in society, %68 has economic problems in sportive facilities, %95.3 thinks that hours of physical education courses are not adequate, %83 considers that sports organizations among schools would be benefical for national sports.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Sport; Physical Education; Society; Hours of Physical Education Courses.